Impact of the Corona Crisis on Marketing Communication Focused on Tourism - Darázs, Tamás; Šalgovičová, Jarmila (Communication Today, 2021)
Tourism and travelling are among the most affected sectors of national economies worldwide due to the pandemic caused by a disease called COVID-19. Nowadays, we still cannot accurately predict the effects of this negative impact. Although the pandemic arrived relatively unexpectedly, it was still likely to be expected to occur. Perhaps that is why, in this scheme, Nassim Nicholas Taleb described it as a ‘white swan’, something that will almost inevitably occur in the future. Anyone who describes a pandemic as a ‘black swan’ may not have understood the topic well and is trying to clarify the related issues based on insufficient information resources. This study deals with the changes that the new situation has brought to the environment of regional marketing and marketing communication, especially in tourism. The work evaluates the mathematical analysis of data obtained from entities operating in marketing communication in regional marketing and tourism. Based on predetermined hypotheses, this research includes the quantitative and qualitative evaluation of subjects’ responses, providing a comprehensive explanation of the various impacts of the pandemic on the activities of entities whose main activity is to intersect with marketing. It seems interesting that not all changes are negative.